ANALISIS FATWA DEWAN SYARIAH NASIONAL NOMOR: 92/DSN-MUI/IV/2014 TENTANG PEMBIAYAAN YANG DISERTAI RAHN - Ihtiar, Habib Wakidatul (UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
This research is conducted to analyze DSN-MUI law of costing with rahn. This research is a literary research. Literary research itself is a research which use numbers of literatures from library as the main resources. The result of the study are follows : First, law decision of DSN-MUI related to costing with rahn is said to be true, by considering the joint beneft. Second, in this law there is a discrepancy between classic fqh and the result of DSN-MUI agreement. In mudharabah transaction, actually, there is no requirement to immerse rahn. In this law, howefer, rahn is immersed.Keyword: Decisison of DSN No. 92 Tahun 2014, Costing, Rahn